Prediction of shear strength of reinforced concrete beams without shear reinforcement considering bond action of longitudinal reinforcements. Issue 1 (January 2018) - Kim, Hyeong-Gook; Jeong, Chan-Yu; Kim, Min-Jun; Lee, Young-Jun; Park, Jung-Han; Kim, Kil-Hee
The shear strength of concrete beams without shear reinforcement is determined by the shear strength of the concrete compressive zone, the shear force due to dowel action, and the shear force due to aggregate interlock. The existing models and formulas to predict shear strength of concrete beams based on geometric theories related to beam action and arch action that only consider shear resistance in relation to arch action while neglecting dowel action and aggregate interlock have been unable to accurately explain the shear resistance mechanism. This study proposes a more rational shear strength prediction formula that reflects the contribution of each component by linking the bond characteristics of longitudinal reinforcements based on the size effect and stress changes in longitudinal reinforcement to dowel action. The precision of the proposed formula was assessed by carrying out experiments with the shear-span-to-depth ratio ( a / d  = 2.0, 2.5, 3.0, and 4.0) as a variable. A ratio of shear bond failure distance to effective depth and the shear strength of concrete beams without shear reinforcement were compared to those obtained from the proposed prediction formula. As a result, it was confirmed that the proposed formula gives rational predictions for each shear contribution and exhibits a high accuracy compared to previous experimental results.